2001
DOI: 10.1046/j.1469-0705.2001.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum analysis of heart rate and blood flow velocity variability measured in the umbilical and uterine arteries in early pregnancy: a comparative study

Abstract: Objective To compare power spectral derived variability parameters from the fetal side of the placental circulation with those from the maternal side of the placental circulation, during early pregnancy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The RI has been used in obstetrics and in nephrology to give a numerical value for the diastolic component in the umbilical arteries and arteries of the transplanted kidney (21, 23). In these two parts of the body, the arteries supply a low resistance arterial bed where flow must be present throughout the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The RI has been used in obstetrics and in nephrology to give a numerical value for the diastolic component in the umbilical arteries and arteries of the transplanted kidney (21, 23). In these two parts of the body, the arteries supply a low resistance arterial bed where flow must be present throughout the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic and parasympathetic control of FHR variability via the sinoatrial node results in moment-to-moment or beat-to-beat oscillation of the FHR (1,2,5). Such regulation normally varies with fetal behavioral state (2), reninangiotensin system (6)(7)(8), and gestational age (9,10). Of clinical interest, FHR variability has been considered as a useful measurement for fetal health in either antepartum or intrapartum, and the decrease or disappearance of FHR variability has been linked to fetal distress (11,12).…”
mentioning
confidence: 99%
“…Such similarities included a peak at the maternal respiration frequency in both spectra (Struijk et al 2001). This study suggested that intervillous pressure fluctuations might induce umbilical flow velocity variability.…”
Section: Introductionmentioning
confidence: 84%